Genomic Epidemiology of Invasive Methicillin-Resistant Staphylococcus aureus Infections Among Hospitalized Individuals in Ontario, Canada. (20th May 2020) - Guthrie, Jennifer L; Teatero, Sarah; Hirai, Sotaro; Fortuna, Alex; Rosen, Daniel; Mallo, Gustavo V; Campbell, Jennifer; Pelude, Linda; Golding, George; Simor, Andrew E; Patel, Samir N; McGeer, Allison; et al.
Abstract: Background: Prevention and control of methicillin-resistant Staphylococcus aureus (MRSA) infections remain challenging. In-depth surveillance integrating patient and isolate data can provide evidence to better inform infection control and public health practice. Methods: We analyzed MRSA cases diagnosed in 2010 ( n  = 212) and 2016 ( n  = 214) by hospitals in Ontario, Canada. Case-level clinical and demographic data were integrated with isolate characteristics, including antimicrobial resistance (AMR), classic genotyping, and whole-genome sequencing results. Results: Community-associated MRSA (epidemiologically defined) increased significantly from 23.6% in 2010 to 43.0% in 2016 ( P  < .001). The MRSA population structure changed over time, with a 1.5× increase in clonal complex (CC)8 strains and a concomitant decrease in CC5. The clonal shift was reflected in AMR patterns, with a decrease in erythromycin (86.7% to 78.4%, P  = .036) and clindamycin resistance (84.3% to 47.9%, P  < .001) and a >2-fold increase in fusidic acid resistance (9.0% to 22.5%, P  < .001). Isolates within both CC5 and CC8 were relatively genetically diverse. We identified 6 small genomic clusters—3 potentially related to transmission in healthcare settings. Conclusions: Community-associated MRSA is increasing among hospitalized individuals in Ontario. Clonal shifting from CC5 to CC8 has impacted AMR. We identified a relatively high genetic diversity and limited genomic clustering within these dominant CCs. Abstract : We describe the changing epidemiology of MRSA in Ontario, Canada. CC5 MRSA strains were replaced by CC8 strains, thereby shifting antimicrobial resistance patterns. Genome sequencing revealed a large strain diversity and few genomic clusters.